THE EFFECT OF A TRAINING CURRICULUM ACCOMPANYING RUBBER ROPES ON THE DEVELOPMENT OF ARMS SKILL AND SOME PHYSIOLOGICAL VARIABLES AMONG JUNIOR CRAWL SWIMMERS - Ammar Ali Ismael Al-Tameemi; Ghassan Habeeb Abdul wahhab; Munadhil Adil Kasim (Proximus Journal Publishing, 2025)
The aim of this study was to identify the effect of the training method designed by the researcher on the elbow skills and some physiological variables of the freestyle for swimmers from Al-Amara Sports Club and Almajar Alkabir Sports Club in the Misan Governorate. The study was carried out in the 2021/2022 season, with a purposive sample of 12 swimmers from the aforementioned clubs. Half of the participants (6 swimmers) were assigned to the experimental group and the other half (6 swimmers) were assigned to the control group. The training programme consisted of 3 sessions per week over 8 weeks. Previous to and following the intervention physical and skill tests were measured. Data were collected and then analyzed by a statistical packages program (SPSS). Results of the study showed that the rubber rope training program was effective (P <0.05) on all the variables of the experimental group participants. QI initiatives were associated with this change, as indicated by significant differences between pre- and post-tests in favor of post-tests. Results of the study showed that the traditional program had significant effect on all the variables measured. Moreover, differences in all variables between the experimental group, control group, as well as high used of innovative experimental group member were significant on the 0.01 level. The researchers suggest that muscle strength in the arms should be higher priority during the sports season in developing the training program. This is because it directly contributes to improving performance and achieving records, as well as when designing specialized teaching programs. Individuals who participate in swimming clubs and members of swimming teams>
Keywords: Training Curriculum; Accompanying Rubber Ropes; Physiological Variables